Analysis of spatial envelope rainfall : intensity : duration : frequency curves for Singapore - Goh, Jeriel Kai Jun (2015)
The objective of this study is the analysis and derivation of the spatial rainfall Intensity-Duration-Frequency curve (IDF) relationship patterns in Singapore. The Rainfall-Intensity-Duration-Frequency curve (IDF curve) is one of the commonly utilized tools in the field of Water Resource Engineering. The.IDF curve represents in graphical form the probability of occurrence of a given rainfall intensity. It is used to estimate the return period of a rainfall event or rainfall amount. The study of the Intensity-Duration-Frequency rainfall relationship is applied in the design, development and operations of water resource projects like the storm drainage systems in Singapore. The main objective of this project is to use the different approaches in the comparison between IDF curves in Singapore. This is done to observe if the current method of using the Gumbel distribution to derive Singapore’s IDF curve is an accurate representation in modelling future rainfall patterns. Because of the unpredictability of climate change, it may not be an accurate representation to use historical data to model future rainfall data. As such this study seeks to analyse if the current overall IDF curve is an accurate representation of the different regions' rainfall in Singapore. It also discusses the viability of using the Maximum Envelope IDF curve in place of the Singapore IDF curve.